FUNCTIONAL RESULTS OF ENDOSCOPIC EXTRAPERITONEAL RADICAL INTRAFASCIAL PROSTATECTOMY - D. V. Perlin; V. P. Zipunnikov; I. N. Dymkov; A. O. Shmanev (Вестник урологии, 2018)
Introduction. Endoscopic radical prostatectomy is a highly effective treatment for localized prostate cancer. Intrafascial prostate dissection ensures early recovery of urine continence function and erectile function. This article sums up our own experience of performing intrafascial endoscopic prostatectomy.Materials and methods. 68 patients have undergone this procedure.Results. 12 months after surgery 88.2 % of the patients were fully continent, 11.7 % had symptoms of minimal stress urinary incontinence. We encountered no cases of positive surgical margins and two case of biochemical recurrence of the disease.Conclusion. Oncologically intrafascial endoscopic radical prostatectomy is as effective as other modifications of radical prostatectomy and has the benefits of early recovery of urine continence function and erectile function.